Dual tasking impairments are associated with striatal pathology in Huntington's disease. Issue 9 (14th August 2020) - Lo, Johnny; Reyes, Alvaro; Pulverenti, Timothy S.; Rankin, Timothy J.; Bartlett, Danielle M.; Zaenker, Pauline; Rowe, Grant; Feindel, Kirk; Poudel, Govinda; Georgiou‐Karistianis, Nellie; Ziman, Mel R.; Cruickshank, Travis M.
Abstract: Background: Recent findings suggest that individuals with Huntington's disease (HD) have an impaired capacity to execute cognitive and motor tasks simultaneously, or dual task, which gradually worsens as the disease advances. The onset and neuropathological changes mediating impairments in dual tasking in individuals with HD are unclear. The reliability of dual tasking assessments for individuals with HD is also unclear. Objectives: To evaluate differences in dual tasking performance between individuals with HD (presymptomatic and prodromal) and matched controls, to investigate associations between striatal volume and dual tasking performance, and to determine the reliability of dual tasking assessments. Methods: Twenty individuals with HD (10 presymptomatic and 10 prodromal) and 20 healthy controls were recruited for the study. Individuals undertook four single and dual task assessments, comprising motor (postural stability or force steadiness) and cognitive (simple or complex mental arithmetic) components, with single and dual tasks performed three times each. Participants also undertook a magnetic resonance imaging assessment. Results: Compared to healthy controls, individuals with presymptomatic and prodromal HD displayed significant deficits in dual tasking, particularly cognitive task performance when concurrently undertaking motor tasks ( P < 0.05). The observed deficits in dual tasking were associated with reduced volume in caudate and putamen structures ( P < 0.05), however, not with clinical measures of disease burden. An analysis of the reliability of dual tasking assessments revealed moderate to high test–retest reliability [ICC: 0.61‐0.99] for individuals with presymptomatic and prodromal HD and healthy controls. Conclusions: Individuals with presymptomatic and prodromal HD have significant deficits in dual tasking that are associated with striatal degeneration. Findings also indicate that dual tasking assessments are reliable in individuals presymptomatic and prodromal HD and healthy controls.